Matizes e (pre) conceitos da mulata nas obras A escrava Isaura e O cortiço - Fonseca, Felisberto Augusto da (2006)
This dissertation proposes an analysis of the novels A Escrava Isaura by Bernardo Guimarães and O Cortiço by Aluísio Azevedo, and it has as support for reflection an investigation about of the “shades” and of the prejudice of the mullata in the respective works. Initially, reflections are done about the literary art, finding the context in the period of publishing of the works. The analysis of the “shades” and of the prejudice of the mullata performed by characters Isaura and Rita Baiana, tries to emphasize and to estimate the different approaches done by authors of the XIX century. This study – when it focus the characters Isaura and Rita Baiana – discusses the language used by the authors in their plots and dialogues, put in scene reflections and it uncovers the racial prejudice in Brazilian society in the second half of XIX century. These elements contribute to validate the literary art as an important presentation to analyse the time and the societies, among others.